2011
DOI: 10.1097/fbp.0b013e328349ab37
|View full text |Cite
|
Sign up to set email alerts
|

Role of training dose in drug discrimination

Abstract: Drug discrimination has been an important technique in behavioural pharmacology for at least 40 years. The characteristics of drug-produced discriminative stimuli are influenced by behavioural and pharmacological variables, including the doses used to establish discriminations. This review covers studies on the effects of varying the training dose of a drug in a search for general principles that are applicable across different drug classes and methodological approaches. With respect to quantitative changes, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 126 publications
6
53
1
Order By: Relevance
“…Further, sensitivity to a moderate alcohol dose (1 g/kg) can be restored by pharmacological activation of mGluR5, perhaps suggesting alleviation, in part, of the functional consequence of downregulated mGluR5. Importantly, alcohol is a complex stimulus cue and different receptor systems modulate sensitivity to different alcohol doses (eg, high vs low; cf, Grant, 1999;Stolerman et al, 2011). Therefore, it will be important to extend the present findings to higher alcohol training doses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, sensitivity to a moderate alcohol dose (1 g/kg) can be restored by pharmacological activation of mGluR5, perhaps suggesting alleviation, in part, of the functional consequence of downregulated mGluR5. Importantly, alcohol is a complex stimulus cue and different receptor systems modulate sensitivity to different alcohol doses (eg, high vs low; cf, Grant, 1999;Stolerman et al, 2011). Therefore, it will be important to extend the present findings to higher alcohol training doses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comprehensive review by Stolerman et al (2011) summarizes several key principles derived from research on the role of training dose in drug discrimination. Notably, higher training doses tend to produce enhanced discrimination accuracy, whereas lower training doses tend to produce lower ED 50 values with the training drug and enhanced sensitivity in stimulus generalization tests with other test compounds.…”
Section: Discussionmentioning
confidence: 99%
“…One of those factors is the dose of the drug used for training (see Stolerman et al, 2011 for a recent review). For example, Schechter (1997) found that the dose-effect functions for cocaine, d- amphetamine, and methamphetamine were shifted to the left in rats trained to discriminate a low dose (2.0 mg/kg) relative to a high dose of cocaine (10.0 mg/kg) from saline.…”
Section: Drug Discriminationmentioning
confidence: 99%